2013
DOI: 10.1093/pcp/pcs189
|View full text |Cite
|
Sign up to set email alerts
|

A Computational and Experimental Approach Reveals that the 5′-Proximal Region of the 5′-UTR has a Cis-Regulatory Signature Responsible for Heat Stress-Regulated mRNA Translation in Arabidopsis

Abstract: Translation of specific plant mRNAs is differentially regulated under certain abiotic stress conditions such as heat, oxygen deprivation and dehydration. The majority of transcripts exhibit varying degrees of translational repression, whereas a subset of transcripts escape such repression and remain actively translated. The underlying mechanisms that mediate this control, and in particular the identities of the regulatory RNA elements involved, remain poorly understood. Using a combined computational and exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…This can be achieved by carrying out a series of mutations in 59UTR (Dvir et al, 2013;Kim et al, 2014) in order to identify important regions for differential mRNA translation during seed germination or dormancy maintenance. Such an approach has already proved to be efficient for demonstrating the role of 59UTR in the regulation of mRNA translation during heat stress in Arabidopsis (Khurana et al, 2013;Matsuura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by carrying out a series of mutations in 59UTR (Dvir et al, 2013;Kim et al, 2014) in order to identify important regions for differential mRNA translation during seed germination or dormancy maintenance. Such an approach has already proved to be efficient for demonstrating the role of 59UTR in the regulation of mRNA translation during heat stress in Arabidopsis (Khurana et al, 2013;Matsuura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We opted to study heat stress because it has been well characterized in Arabidopsis at the level of translation (Matsuura et al, 2010(Matsuura et al, , 2013Mittler et al, 2012), and because thermotolerance has been shown to be induced by heating seedlings to 38°C for 90 min (Larkindale and Vierling, 2008), a timescale that is easily accessible to BONCAT analysis (Fig. 2B).…”
Section: Identifying Candidate Proteins Involved In Thermotolerance Amentioning
confidence: 99%
“…To give one example, upon heat stress, heat shock protein mRNAs continue to be actively translated, whereas other mRNAs are sequestered into stress granules and translationally suppressed (Nover et al, 1989;Matsuura et al, 2010a;Sormani et al, 2011a). Some sequence elements responsible for continued translation under heat shock reside in the 5' UTR (Matsuura et al, 2013). For example, in Arabidopsis HSP81-3, a 47 nucleotide (nt) pyrimidine rich element stimulates cap-independent translation after heat shock (Matsuura et al, 2008).…”
Section: Translational Control In Response To Abiotic Stressmentioning
confidence: 99%
“…To date, such elements qualify as cap-independent, i.e., they may still involve eIF4E and scanning (Vanderhaeghen et al, 2006;Mardanova et al, 2008). For example, the preferential translation of a heat shock protein mRNA at high temperature is mediated by a feature of its 5' UTR that renders its translation cap-independent (Stuger et al, 1999;Dinkova et al, 2005;Matsuura et al, 2008;Matsuura et al, 2013).…”
Section: Cap-independent Translation Initiationmentioning
confidence: 99%